2000
DOI: 10.1159/000018844
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Bolus Glutamine Supplementation on the Postresectional Adaptation of Small Bowel Mucosa in Rats Receiving Chow ad libitum

Abstract: Objective: Early postoperative enteral feeding has been reported to stimulate intestinal mucosa proliferation. Dietary components influence the intestinal adaptive response after resection and glutamine is a preferential nutrient to enterocytes. The purpose of this study was to evaluate the effects of bolus glutamine supplementation on intestinal adaptation. Methods: Male Wistar rats underwent a 65% small bowel resection. The rats were divided into three groups receiving glutamine 2 g/kg/day, isonitrogenous gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…7,28,29,30 Yang et al (2000), after administering 2 g/kg/day of glutamine by enteral bolus to rats undergoing extensive intestinal resection, did not observe improvement in intestinal adaptation after the 10th day post surgery. 31 Regarding the toxic effect of cyclosporin on the intestinal epithelium, Zhang et al (1995) studied rats undergoing small bowel transplant while using immunosuppression with cyclosporin (15 mg/kg). Animals received either elemental diet with 2% glutamine or the same diet with balanced nonessential amino acids (without glutamine).…”
Section: Discussionmentioning
confidence: 99%
“…7,28,29,30 Yang et al (2000), after administering 2 g/kg/day of glutamine by enteral bolus to rats undergoing extensive intestinal resection, did not observe improvement in intestinal adaptation after the 10th day post surgery. 31 Regarding the toxic effect of cyclosporin on the intestinal epithelium, Zhang et al (1995) studied rats undergoing small bowel transplant while using immunosuppression with cyclosporin (15 mg/kg). Animals received either elemental diet with 2% glutamine or the same diet with balanced nonessential amino acids (without glutamine).…”
Section: Discussionmentioning
confidence: 99%
“…Since enteral glutamine can be readily absorbed by small intestinal epithelium, and glutamine oxidation 70 ISSN 1007 -9327 CN 14 -1219/ R World J Gastroentero February 2001 Volume 7 Number 1 stimulates enterocyte Na + /H + exchange, leading to a high rate of electroneutral NaCl absorption in healthy and diseased jejunum [20] , we studied the effect of enteral glutamine perfusion on the remnant intestinal mucosal structure during TPN. Because previous studies have not confirmed the b e n e f i c i a l e f f e c t o f e n t e r a l g l u t m i n e supplementation during EN [21][22][23][24][25] , we also studied the effect of adding extra glutamine to nutritioncomplete enteral diet. Our results confirmed the existence of TPN induced intestinal hypoplasia, which was indicated by significantly lower villi in both jejunum and ileum and markedly shallower crypts in jejunum in TPNcon group compared with ENcon group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that glutamine supplementation protects the GALT atrophy and IgA depletion that result from long-term TPN and enhances nutrient absorption [17,18]. However, conflicting results have been reported in terms of enteral or parenteral glutamine administration in animal studies, as well as clinical trials that evaluated intestinal adaptation after massive intestinal resection [4,5,[19][20][21][22][23][24][25][26][27]. Therefore, the efficacy of Gln administration in the management of SBS is currently controversial.…”
Section: Some Trophic Factors (Ie Growth Hormone [Gh] Insulinlike mentioning
confidence: 99%
“…These results may be related to the lack of additional growth factors, nutrients, and supportive enteral or parenteral nutrition. To remedy this problem, a glutamine and GH combination seems to be the most frequently studied combination, although conflicting results are reported (Table 4) [5,9,10,[25][26][27]33,[48][49][50]. Although some authors report enhanced intestinal adaptation either with enteral [25] or parenteral [5] glutamine supplementation alone, others report no effect on intestinal adaptation [9,10,26,27,33,50].…”
Section: Gln -Glutamine; Gh -Growth Hormon; En -Enteral Nutrition; Hgmentioning
confidence: 99%
See 1 more Smart Citation